Frequency of Endoscopic Gastric Neoplasms in Five Years at JPMC (Medical Forum Monthly, 2024)
Objectives: Gastric cancer is among the most common malignancies in Pakistan. The aim of our study are i) to document different histological types of gastric malignancies as per age and sex ii) discuss its possible association in patients who underwent endoscopy and iii) compare our data with local and abroad studies. Study Design: Retrospective study. Place and Duration of Study: This study was conducted in the Department of Pathology, Basic Medical Science Institute, Jinnah Postgraduate Medical Centre, Karachi, Pakistan, from 1st January2003 to 31st December 2007. Materials and Methods: A total of 740 cases of gastric endoscopic biopsies were received for histopathological evaluation at the Department of Pathology, Basic Medical Science Institute, JPMC, Karachi. Out of these cases, a total of 70 gastric neoplasms were separated, analyzed and classified according to the WHO classification system and their relative frequencies were recorded. Results: Gastric adenocarcinoma was the commonest neoplasm with male predominance in 5th to 7th decade of life, account for 88.57% (62/70) of all gastric neoplasms. Gastric lymphoma was the second common with 8.57%(06/70) and gastric carcinoid was least common with 1.43%(1/70) of all gastric neoplasms. Conclusion: This study highlights that adenocarcinoma is the most common gastric malignancy seen in most high risk group includes elderly males followed by lymphoma with no gender difference. So we advise regular endoscopic biopsies surveillance at least in high risk age group for the early detection of cancer.